A Comprehensive, Tailored Approach to New Faculty Mentoring - Kathryn L. Hope (Academic Chairpersons Conference Proceedings, 2016)
The presenters will discuss the best practices in the development of a comprehensive mentoring plan for new faculty that address teaching, service, research, and practice. A case study and discussion will address how to develop and tailor a mentoring plan according to faculty role, rank, education, and experience.
Keywords: New faculty mentoring; faculty development; academic mentoring